IoT-based Smart Chili Farm Monitoring using Arduino and GSM Module / Muhammad Baihaqi Bakar and Rashidah Ramle - Bakar, Muhammad Baihaqi; Ramle, Rashidah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
This research has developed a wireless communication unit for transferring data from sensors, such as the DHT11 temperature and humidity sensor, the yl-69 soil moisture sensor, and the pH level sensor, in order to create a monitoring system for chili farms. The goal of this study is to establish a system for systematically gathering and managing data pertaining to chili farms. The goals of the IoT-based Smart Chili Farm Monitoring Using Arduino and GSM Module research is to provide farmers with the recognition that they need to be more vigilant in their monitoring of the chili plants. The purpose of this research is to design, build, and test a temperature, humidity, soil moisture, and soil pH level sensor-based alert system for a chili farm using an Arduino and a Global System for Mobiles (GSM) Module, and then to assess the system's functionality and applying the Technology Acceptance Model. This prototype is useful in allowing users to keep tabs on and modify variables including ambient temperature, humidity, soil moisture, and pH. In conclusion, this study has built an Internet of Things (IoT)-based Smart Chili Farm Monitoring system using Arduino and GSM Module to help farmers and other users.